(untitled) (International Journal of Occupational Safety and Health, 2023)
Introduction: Burnout is most common among healthcare workers and is characterized by emotional fatigue, depersonalization and low personal accomplishment impacting behaviors also the work environment. This study aimed to analyze areas of work-life and burnout among dentists in dental hospitals. Methods: A cross-sectional survey study was conducted on 72 dentists in a dental hospital in Denpasar. An online questionnaire containing the Maslach Burnout Inventory and the Areas of Work Life Survey by Michael Leiter and Christina Maslach to estimate burnout and work life was used for data collection from April-May 2022. Multiple linear regression was used to evaluate the association. Results: The work-life area category had a score of 3.45, while the dentist’s average score for burnout had a mean value of 4.15. Workload, control, rewards, community, fairness, and values were associated with burnout. The control dimension showed the strongest correlation to burnout. The reward dimension had the most significant role in burnout. All dimensions of the work-life area are predictors of dentist burnout. Conclusion: Based on the finding of this study, all of the dimensions of work life can potentially cause burnout in dentists. A reward is the most dominant variable in the emergence of burnout. Management needs to set policies to reduce burnout for dentists at work.